The impact of performance appraisal practices on employee performance: A case study of King Abdulaziz City for Science and Technology in Saudi Arabia (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study aims to analyze the impact of performance appraisal practices on employee performance at King Abdulaziz City for Science and Technology (KACST) in Saudi Arabia, within the framework of efforts to develop institutional performance and enhance the productivity of human resources. The study focused on several dimensions of performance appraisal practices, namely: clarity of appraisal, fairness and objectivity of appraisal, feedback, and the use of technology in appraisal, with the goal of determining their impact on improving employee performance within the organization. The study adopted a descriptive-analytical approach and used a questionnaire as the primary data collection tool from a sample of 250 employees from various departments and job levels within KACST.The results indicated a high level of performance appraisal practices within KACST. The analysis revealed a strong and positive correlation between performance appraisal practices and employee performance (r = 0.773, sig = 0.01), demonstrating that developing performance appraisal systems directly contributes to improving overall employee performance. The study also found statistically significant correlations between each dimension of evaluation practices and employee performance. The results indicate that clear evaluation criteria, fairness in application, the provision of constructive feedback, and the use of modern technological tools are essential factors for improving both individual and organizational performance.In light of these findings, the study recommends strengthening electronic evaluation systems, developing precise and transparent evaluation criteria, and training leaders and supervisors to apply performance evaluation practices objectively and fairly. This will contribute to raising employee performance levels and achieving the goals of King Abdulaziz City for Science and Technology (KACST) within its strategic vision of supporting excellence and innovation.
Keywords: Performance Evaluation Practices; Evaluation Clarity; Fairness and Objectivity; Feedback; Use of Technology in Evaluation; Employee Performance; King Abdulaziz City for Science and Technology (KACST); Saudi Arabia